Neural effects of the CSMD1 genome‐wide associated schizophrenia risk variant rs105032531. Issue 6 (10th July 2013) - Rose, Emma J.; Morris, Derek W.; Hargreaves, April; Fahey, Ciara; Greene, Ciara; Garavan, Hugh; Gill, Michael; Corvin, Aiden; Donohoe, Gary
ABSTRACT The single nucleotide polymorphism rs10503253 within the CUB and Sushi multiple domains‐1 (CSMD1) gene on 8p23.2 has been identified as genome‐wide significant for schizophrenia (SZ). This gene is of unknown function but has been implicated in multiple neurodevelopmental disorders that impact upon cognition, leading us to hypothesize that an effect on brain structure and function underlying cognitive processes may be part of the mechanism by which CMSD1 increases illness risk. To test this hypothesis, we investigated this CSMD1 variant in vivo in healthy participants in a magnetic resonance imaging (MRI) study comprised of both fMRI of spatial working memory (N = 50) and a voxel‐based morphometry investigation of grey and white matter (WM) volume (N = 150). Analyses of these data indicated that the risk "A" allele was associated with comparatively reduced cortical activations in BA18, that is, middle occipital gyrus and cuneus; posterior brain regions that support maintenance processes during performance of a spatial working memory task. Conversely, there was an absence of significant structural differences in brain volume (i.e., grey or WM). In accordance with previous evidence, these data suggest that CSMD1 may mediate brain function related to cognitive processes (i.e., executive function); with the relatively deleterious effects of the identified "A" risk allele on brain activity possibly constituting part of the mechanism by which CSMD1 increases schizophrenia risk. © 2013 Wiley Periodicals, Inc.